Effect of sprinkler with fan on growth, physiology and behaviour of Murrah buffalo calves - singh, navav; Roshan Kumar Bhuradia; Sanjita Sharma; Sanjay Kumar Choudhary; Nischay Singh; Gireesh Joshi; Anita Kavia (Indian Journal of Dairy Science, 2023)
The aim of the present study was to investigate the effect of sprinkler with ceiling fans on the growth performance, physiological responses and behaviour of Murrah buffalo calves. For this study, a total of twelve Murrah buffalo female calves were selected based on the age and body weight and allocated to two treatments (n=6 each). In the first treatment (T1), the calves were provided with sprinkler with fan. While, in second treatment called control (T0), the calves were not provided with any cooling system. The average daily was greater in T1 than T0 calves on week (w) 3 (P=0.01), w 4 (P=0.03), w 5 (P=0.04), w 6 (P=0.02), w 7 (P=0.01) and w 8 (P=0.05). While it was similar between the calves of two groups on the w 1 (P= 0.32), w 2 (P=0.31), w 9 (P=0.16), w 10 (P=0.19), w 11 (P=0.12), w 12 (P=0.1).The overall eye temperature was significantly (P<0.05) higher in control group (37.42±0.04 ºC) than treatment group (36.42±0.13 ºC) calves. Similarly, the overall muzzle (P=0.01) and skin temperature (P=0.001) was also significantly higher in control calves as compared to treatment calves.The average respiration rate was lower (P<0.05) in T1 (22.83±0.18 No./min) than in T0 (30.83±0.12 No./min) calves. Similarly, overall pulse rate was also lower (P<0.05) in T1 (38.36±0.11 No./min) as compared to T0 (60.19±0.13 No./min) calves.The average time spent on eating, ruminating and resting was significantly greater in T1 than in T0 calves. In conclusion, the provision of sprinkler with fan reduces physiological response along with body temperatures. Consequently, it improves the growth performance and helps in normal behavioural expression of the buffalo calves.